Model Penilaian dan Pemilihan Trade Show Bagi Industri Kreatif di Sektor Mode - Afrin Fauzya Rizana; Rayinda P. Soesanto; Amelia Kurniawati (Jurnal Ilmiah Teknik Industri, 2017)
The article identifies the criteria for choosing a trade show and develops a basic model of exhibition selection for creative industry players before deciding to participate in a trade show. It is necessary to ensure that expenses in terms of business, money, and time, will be worth the results. Based on literature review and interviews, six criteria were used, namely location, booth position, organizational reputation, cost estimation, prestige, and reputation of other participants. After selection criteria are identified, then calculations are performed to measure the criteria weight by using the AHP approach. Based on weight calculations, it was found that booth positions had the highest importance weight, followed by trade show location, organizers reputation, cost estimation, prestige and reputation of other participants. The weight value is then used to calculate the trade show's prediction value. The predicted value generated from the model is then compared to the value of the past data. The model has an accuracy rate of 89% and does not have a significant difference between the value generated by the model and the value of the past data.